Permintaan Beras di Provinsi Jambi (Penerapan Partial Adjustment Model) - Wasi Riyanto; M. Ridwansyah; Etik Umiyati (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2013)
The purpose of this study is to determine the effect of price of rice, flour prices, population, income of population and demand of rice for a year earlier on rice demand, demand rice elasticity and rice demand prediction in Jambi Province. This study uses secondary data, including time series data for 22 years from 1988 until 2009. The study used some variables, consist of rice demand (Qdt), the price of rice (Hb), the price of wheat flour (Hg), population (Jp), the income of the population (PDRB) and demand for rice the previous year (Qdt-1). The make of this study are multiple regression and dynamic analysis  a Partial Adjustment Model, where the demand for rice is the dependent variable and the price of rice, flour prices, population, income population and demand of rice last year was the independent variable. Partial Adjustment Model analysis results showed that the effect of changes in prices of rice  and flour are not significant  to  changes in demand for rice. The population and demand of rice the previous year has positive and significant impact on demand for rice, while revenues have negative and significant population of rice demand. Variable price of rice, earning population and the price of flour is inelastic the demand of rice, because rice is not a normal good but as a necessity so that there is no substitution of goods (replacement) of rice with other commodities in Jambi Province. Based on the analysis, it is recommended to the government to be able to control the rate of population increase given the variable number of people as one of the factors that affect demand for rice.It is expected that the  government also began  to  socialize  in a lifestyle  of  non-rice food consumption to control the increasing amount of demand for rice. Last suggestion, the government developed a diversification of staple foods other than rice. Keywords: Demand, Rice, Income Population